CLINICAL AND MICROBIOLOGICAL PARALLELS IN PREMATURE BIRTHS - Gromova, A.M.; Mityunina, N.I.; Nesterenko, L.A.; Tarasenko, K.V.; Talash, V.V. (World of Medicine and Biology, 2013)
Purpose - to identify risk factors for premature birth. The course of pregnancy, birth and the neonatal period. Microbiological studies of fetal membranes and placenta indicate their bacterial contamination during premature depending on duration of waterless period. One of the stages in the reduction of the reserve of preterm birth and neonatal morbidity is pregravid preparation and remediation of sources of infection, including conditional - pathogenic bacterial flora.